2022
DOI: 10.1038/s41598-022-13635-x
|View full text |Cite
|
Sign up to set email alerts
|

Screening and purification of NanB sialidase from Pasteurella multocida with activity in hydrolyzing sialic acid Neu5Acα(2–6)Gal and Neu5Acα(2–3)Gal

Abstract: Study on sialidases as antiviral agents has been widely performed, but many types of sialidase have not been tested for their antiviral activity. Pasteurella multocida NanB sialidase is one such sialidase that has never been isolated for further research. In this study, the activity of NanB sialidase was investigated in silico by docking the NanB sialidase of Pasteurella multocida to the Neu5Acα(2–6)Gal and Neu5Acα(2–3)Gal ligands. Additionally, some local isolates of Pasteurella multocida, which had the NanB … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 54 publications
2
15
1
Order By: Relevance
“…Based on the calculation of the speci c activity and comparison between total sialidase activity and total protein, the results of puri cation showed that at least 258 mU/ml was obtained. The enzymes obtained in this study are in accordance with previous studies which have succeeded in producing sialidase derived from Pasteurella multocida bacterial cells (Nugroho et al 2022). Observation of cytotoxicity in MDCK cells was carried out by gradual doses 32 mU/ml, 64 mU/ml, 129 mU/ml, and 258 mU /ml of sialidase.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…Based on the calculation of the speci c activity and comparison between total sialidase activity and total protein, the results of puri cation showed that at least 258 mU/ml was obtained. The enzymes obtained in this study are in accordance with previous studies which have succeeded in producing sialidase derived from Pasteurella multocida bacterial cells (Nugroho et al 2022). Observation of cytotoxicity in MDCK cells was carried out by gradual doses 32 mU/ml, 64 mU/ml, 129 mU/ml, and 258 mU /ml of sialidase.…”
Section: Resultssupporting
confidence: 90%
“…The spectrophotometer was used to measure absorbance readings at a wavelength of 405 nm. (Kurnia et al 2022a;Nugroho et al 2022) The effect of sialidase on viral replication was evaluated by exposing MDCK cells, previously treated with the enzyme and subsequently challenged with the H9N2 virus to evaluate the effectiveness of sialidase in hindering viral replication. Monolayer MDCK cells on 96-well plates.…”
Section: Bacterial Culture and Sialidase Puri Cationmentioning
confidence: 99%
See 1 more Smart Citation
“…The sequencing of amplicons that only showed positive NanH, NanI, and NanJ of each isolate was performed by the 1st base sequencing service agency in Malaysia. Sequencing data were analyzed using MEGA X and Bioedit software to compare the nucleotide sequence of the current isolate with the sialidase gene of the C. perfringens isolate in the GenBank database [12 , 20] .…”
Section: Methodsmentioning
confidence: 99%
“…The total RNA was quantified on a NanoDrop spectrophotometer (BioDrop, UK) with a wavelength of 260 nm. Quantitative real time-polymerase chain reaction (qRT-PCR) assays were performed using similar procedure from Nugroho, et al 47 The BDNF mRNA expression analysis was performed using qRT-PCR applied Biosystem with ReverTra ® qPCR RT Master Mix/gDNA remover kit (Toyobo Bio-Tech). The presence of BDNF and GAPDH was detected with a primary from: BDNF -NeuroD1, forward 5’-AAGCCATGAATGCAGAGGAGGACT-3’; reverse: AGCTGCAGGCAGCCGGCGACC), GAPDH forward 5’-TGCACCACCAACTGCTTAGC-3’ and reverse 5’-GGCATGGACTGTGGTCATGAG-3’.…”
Section: Methodsmentioning
confidence: 99%